Pendampingan Pembuatan Jalur Evakuasi Guna Mitigasi Bencana Bagi Komunitas Pasar Desa di Lereng Muria - Eva Banowati; Sriyanto Sriyanto; Muhammad Fauzan Ramadhan; Ayu Wulansari Pramita; Lina Adi Wijayanti (Universitas Negeri Semarang, 2024)
Pasar Desa Gerit, also known as Pasar Perkaulaan, is located in Cluwak District - Pati Regency. The market operates once every 36 days, the time chosen following the Javanese calendar called pasar. The market opens every Sunday Legi to Sening Pahing. Visitors have a vow , which is a promise associated with religion[3][4]. The purpose of this activity is to provide assistance to the market community as a preventive measure to mitigate disasters, for example due to man-made disasters [18] or natural disasters. The implementation method is packaged in the form of qualitative socialization, including: socialization by providing disaster mitigation material, FGDs, determining the placement of evacuation routes and gathering points that are easily accessible to the community. Furthermore, the installation of signs by community participants, feedback on a series of activities as an evaluation of the success of the activity. The implication of the activity shows the building of community enthusiasm for socialization, understanding the usefulness of the need for signs, and their placement. In addition, the target audience can practice following the evacuation route to find the shortest way to reach a safe place indicated by the assembly point